2019
DOI: 10.3390/w11112313
|View full text |Cite
|
Sign up to set email alerts
|

Wave Forecasting in Shallow Water: A New Set of Growth Curves Depending on Bed Roughness

Abstract: Forecasting relationships have been recognized as an important tool to be applied together, or not, with complete numerical modelling in order to reconstruct the wave field in coastal areas properly when the available wave data is limited. In recent years, the literature has offered several comprehensive sets of field experiments investigating the form of the asymptotic, depth-limited wind waves. This has made it possible to reformulate the original deep water equations, taking into account the effects of wate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 56 publications
0
4
0
Order By: Relevance
“…Following a rigorous classification, the lagoon of Marano and Grado is a microtidal environment. However, the northern Adriatic Sea is characterized by shallow waters that strongly attenuate the wave motion through bottom friction dissipations [36,37]. As a consequence, the resulting mean wave height has a low average value, thus requiring a smaller tidal range to produce tidal-influenced morphology [2].…”
Section: Study Site and Historical Analysismentioning
confidence: 99%
“…Following a rigorous classification, the lagoon of Marano and Grado is a microtidal environment. However, the northern Adriatic Sea is characterized by shallow waters that strongly attenuate the wave motion through bottom friction dissipations [36,37]. As a consequence, the resulting mean wave height has a low average value, thus requiring a smaller tidal range to produce tidal-influenced morphology [2].…”
Section: Study Site and Historical Analysismentioning
confidence: 99%
“…Furthermore, tidal inlets are fundamental in the morphodynamic processes of the nearby coast and of the lagoon itself. In fact, they act as both sources and sinks of the sediments which are suspended from the bottom by the wave motion, which is locally generated inside the basin or outside in the open sea [2][3][4][5][6][7][8][9][10]. Sediments are then transported by currents that transfer the material into the network of tidal channels or along the shore in the surf zone.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, inside lagoons, where current speed and water depth are relatively low, wind waves become crucial for sediment transport despite their relatively short period [17,18]. In fact, waves locally generated on the shallow tidal flats [19] interact with tidal currents, originating bottom shear stresses able to pick up even the finest sediments [20]; these are then conveyed along the canals, and therefore can penetrate the lagoon ports.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, an accurate wind analysis has been carried out to give a comparative evaluation of any drawbacks due to increased sediment deposition. Petti and co-workers [19,38] showed that fetch loses importance in the generation process of wind waves within a lagoon context, where the shallow water depths considerably limit the wave growth, thus becoming essential for a correct wave description. In this sense, water depth and wind intensity play a major role.…”
Section: Introductionmentioning
confidence: 99%